2020
DOI: 10.1101/2020.01.09.899724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FTO-mediated cytoplasmic m6Amdemethylation adjusts stem-like properties in colorectal cancer cell

Abstract: 20Cancer stem cells (CSCs) are a small but critical cell population for cancer biology since they display 21 inherent resistance to standard therapies and give rise to metastases. Despite accruing evidence 22 establishing a link between deregulation of epitranscriptome-related players and tumorigenic 23 process, the role of messenger RNA (mRNA) modifications dynamic in the regulation of CSC 24 properties remains poorly understood. Here, we show that the cytoplasmic pool of fat mass and 25 obesity-associated pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Recent evidence shows that FTO-mediated m 6 Am demethylation is an important regulatory mechanism in adjusting the stem-like properties of colorectal cancer cells [116], and many clues also imply that m 6 Am also emerges as an essential regulator in GBM (Figure 2, m 6 Am part). For instance, an integrated proteogenomic analysis in 17 GBM patient samples reveals that METTL4 is one of the top-ranked missense mutation genes [77].…”
Section: Rna M 5 C Modification In Gbmmentioning
confidence: 99%
“…Recent evidence shows that FTO-mediated m 6 Am demethylation is an important regulatory mechanism in adjusting the stem-like properties of colorectal cancer cells [116], and many clues also imply that m 6 Am also emerges as an essential regulator in GBM (Figure 2, m 6 Am part). For instance, an integrated proteogenomic analysis in 17 GBM patient samples reveals that METTL4 is one of the top-ranked missense mutation genes [77].…”
Section: Rna M 5 C Modification In Gbmmentioning
confidence: 99%
“…The reduced Siah1 and Fbxo45 further downregulates the EMT-transcription factors Zeb1, and ultimately leads to the development of CRC. In addition, Relier et al ( 164 ) showed that low expression of FTO in CRC cells causes increase of the m 6 Am levels in mRNAs and results in the enhanced malignancy and chemo resistance in CRC cells, which can be partially reversed by inhibition of PCIF1.…”
Section: Links With Gastrointestinal Cancers and Potential Therapeutimentioning
confidence: 99%
“…While there's some controversy as to whether FTO de-methylates m 6 Am, m 6 A, or both in vivo, there is broad agreement that FTO de-methylates m 6 Am and CA-m 6 Am in different types of RNA [35,59,75,89,143,151,152,175]. By combining different methods FTO was convincingly shown to remove methyl groups from m 6 Am in different contexts.…”
Section: Fto An M 6 Am Erasermentioning
confidence: 99%
“…Overexpression of PCIF1 in HEK293T cells led to a ~3fold increase in the m 6 Am to Am ratio showing that overexpression studies could also help determine the in vivo functions of CA-m 6 Am [162]. Finally, altering the levels of CAm 6 Am has effects on mRNA metabolism in vivo [47,153,[161][162][163][164]175]. For example, PCIF1 -/mice are viable but show a pronounced growth defect [164].…”
Section: Functions Of Ca-m 6 Ammentioning
confidence: 99%
See 1 more Smart Citation